Residual stress influence on fatigue lifetimes of electroplated AISI 4340 high strength steel - Voorwald, H. J. C.; Rocha, P. C. F.; Cioffi, M. O. H.; Costa, M. Y. P. (Blackwell Publishing, 2007)
Residual stresses play an important role in the fatigue lives of structural engineering components. In the case of near surface tensile residual stresses, the initiation and propagation phases of fatigue process are accelerated; on the other hand, compressive residual stresses close to the surface may increase fatigue life. In both decorative and functional applications, chromium electroplating results in excellent wear and corrosion resistance. However, it is well known that it reduces the fatigue strength of a component. This is due to high tensile internal stresses and microcrack density. Efforts to improve hard chromium properties have increased in recent years. In this study, the effect of a nickel layer sulphamate process, as simple layer and interlayer, on fatigue strength of hard chromium electroplated AISI 4340 steel hardness - HRc 53, was analysed. The analysis was performed by rotating bending fatigue tests on AISI 4340 steel specimens with the following experimental groups: base material, hard chromium electroplated, sulphamate nickel electroplated, sulphamate nickel interlayer on hard chromium electroplated and electroless nickel interlayer on hard chromium electroplated. Results showed a decrease in fatigue strength in coated specimens and that both nickel plating interlayers were responsible for the increase in fatigue life of AISI 4340 chromium electroplated steel. The shot peening pre-treatment was efficient in reducing fatigue loss in the alternatives studied.
Keywords: AISI 4340; fatigue; hard chromium; nickel; shot peening